Stroke mortality: predictive value of simple laboratory tests and acute physiology, age, chronic health evaluation III scoring system: a hospital based study - Chaurasia, Ajeet K.; Mathur, Manoj K.; Dwivedi, N.C.; Mishra, Manjul (International Journal of Research in Medical Sciences, 2016)
Background: Acute stroke is a heterogeneous condition with respect to prognosis. This study was undertaken with the aim to evaluate the significance of routine simple blood parameters and APACHE (acute physiology, age, chronic health evaluation) III scoring system as methods of prediction of 1-month mortality in stroke patients and to assess the sensitivity and specificity of APACHE III scoring system in predicting short term outcome in critically ill patients having stroke. Methods: Patients of stroke presenting within 48 hours of onset were included in the study irrespective of age, sex or type of stroke. The clinical evaluation, neuroimaging and blood investigations were performed. APACHE III scoring system was applied for each patient to calculate the score for each one. The outcome of the patients at the end of one month was determined as survivors and expired. Results: Among the total 120 cases in the study, 54.16% (n=65) patients survived at the end of one month. The mean APAPCHE III Score among the survivors was 45.3 and in expired patients it was 88.6. Taking a cut-off value of 50, APACHE III Score was significantly associated in predicting the mortality in stroke patients (P-value<0.0001). Conclusions: The study concluded that a low GCS at the time of admission and increased serum creatinine were independent predictors of mortality among patients presenting to the hospital within 48 hours with first time acute stroke. APACHE III scoring system was found to be sensitive and reasonably specific in predicting short term outcome in patients having cerebral stroke.